2020
DOI: 10.1002/eco.2246
|View full text |Cite
|
Sign up to set email alerts
|

Effects of diatoms on erosion and accretion processes in saltmarsh inferred from field observations of hydrodynamic and sedimentary processes

Abstract: Microphytobenthos influence sediment dynamics via their growth and covering on the surface sediment of saltmarshes. To understand the sediment transport and morphological changes resulting from microphytobenthos in a saltmarsh, two parallelly located sites were established to measure the hydrodynamic forces, sediment characteristics and microphytobenthos properties both in winter and summer. Diatoms were not observed at any of the two sites in winter because of their growth cycles. In summer, however, diatoms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 57 publications
0
7
1
Order By: Relevance
“…We infer that the accurate critical erosion shear stress of cohesive sediments with active biological activities can only be obtained by field measurements, therefore, the results from CSM observation are more reliable. Previous studies show that the critical erosion threshold of substrate sediments in the salt marsh zone of this study area ranges from 0.3 to 0.4 N/m 2 based on CSM measurement (Chen et al, 2020), much smaller than our results, this may due to the dissipative and trapping effects of salt marsh that allow the settling of fine-grained sediments (sediment fraction is relatively homogeneous), resulting in a small critical erosion threshold. In summary, the above results indicated that the uneven spatial distribution of erosion threshold caused by physical characteristics of sediments and biological activities provide the foundation of patches formation, while hydrodynamics is the crucial driving force in determining the development, distribution, and destruction of hummocky patches (Figure 11).…”
Section: Hydrodynamicscontrasting
confidence: 87%
“…We infer that the accurate critical erosion shear stress of cohesive sediments with active biological activities can only be obtained by field measurements, therefore, the results from CSM observation are more reliable. Previous studies show that the critical erosion threshold of substrate sediments in the salt marsh zone of this study area ranges from 0.3 to 0.4 N/m 2 based on CSM measurement (Chen et al, 2020), much smaller than our results, this may due to the dissipative and trapping effects of salt marsh that allow the settling of fine-grained sediments (sediment fraction is relatively homogeneous), resulting in a small critical erosion threshold. In summary, the above results indicated that the uneven spatial distribution of erosion threshold caused by physical characteristics of sediments and biological activities provide the foundation of patches formation, while hydrodynamics is the crucial driving force in determining the development, distribution, and destruction of hummocky patches (Figure 11).…”
Section: Hydrodynamicscontrasting
confidence: 87%
“…τ m is expected to be greater than τ c , and τ max to be greater than the vector sum of τ c and τ w (Soulsby and Clarke, 2005). These methods have been successfully applied to estimate mean and maximum bed shear stresses accounting for the attenuation of the near-bed flows by the canopy, including coral reefs (Pomeroy et al, 2017(Pomeroy et al, , 2021, saltmarsh (Chen et al, 2020) and benthic feeding tubes (Egan et al, 2020(Egan et al, , 2021.…”
Section: Hydrodynamic Data Analysismentioning
confidence: 99%
“…Shorelines, as well as the new reserved land brought about by the shoreline expansion, are the most valuable natural resource in the land-ocean interaction areas (Temmerman et al, 2013). As the value provider for ecosystem services (Chen et al, 2020), they could ensure the land demand for increased human survival and development space, provide habitat for fish, birds and benthic organisms, and serve as the buffer zone and natural barrier against marine disasters such as storm surges (Allen, 2000;Costanza, 2006). Therefore, investigating the changes in the key areas of shoreline expansion is necessary for coastal zone environmental planning and ecological conservation (Wang et al, 2012;Addo, 2013;Li et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The hydrodynamic environment in estuaries and coasts determines the direction and destination of suspended sediment transport (Wang et al, 2013;Xiong et al, 2017;Li et al, 2018). Hence, the physical processes of local hydrodynamic-sediment coupling and the corresponding biological responses affect the seaward/ landward trend of coastal wetlands and, therefore, shoreline changes (Chen et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation